2010
DOI: 10.2967/jnumed.110.079004
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Expression of the Human Somatostatin Receptor Subtype-2 Reporter Gene with 68Ga-DOTATOC

Abstract: The human somatostatin receptor subtype 2 (hSSTr2)-68 Ga-DOTATOC reporter system has several attractive features for potential translation to human studies. These include a low expression of hSSTr2 in most organs, a rapid internalized accumulation of 68 Ga-DOTATOC in the SSTr2-expressing cells, and a rapid excretion of unbound radioligand by the renal system. We performed a series of in vitro and in vivo validation studies of this reporter system. Methods: A retroviral vector containing a dual reporter, pQCXhS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 33 publications
1
62
0
Order By: Relevance
“…Over the course of tumor growth, DOTATOC uptake was higher in tumors comprising increasing percentages of SSTR2 + cells ( Figure 2B). PET/CT images showed DOTATOC uptake by tumors and uniformly higher uptake by the kidneys and bladder -consistent with its known biodistribution and renal clearance ( Figure 2C) (19). DOTATOC uptake values, as measured by %ID/cm 3 , agreed with visual assessments of PET/CT images over the course of tumor growth and correlated with increasing SSTR2 + percentages within the tumors ( Figure 2, B and C, and Supplemental Figure 2).…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Over the course of tumor growth, DOTATOC uptake was higher in tumors comprising increasing percentages of SSTR2 + cells ( Figure 2B). PET/CT images showed DOTATOC uptake by tumors and uniformly higher uptake by the kidneys and bladder -consistent with its known biodistribution and renal clearance ( Figure 2C) (19). DOTATOC uptake values, as measured by %ID/cm 3 , agreed with visual assessments of PET/CT images over the course of tumor growth and correlated with increasing SSTR2 + percentages within the tumors ( Figure 2, B and C, and Supplemental Figure 2).…”
Section: Resultssupporting
confidence: 69%
“…Therefore, to approximate the DOTATOC-based detection limit of tumor-infiltrating SSTR2-transduced T cells, we utilized mosaic tumor xenografts of Jurkat T cells with increasing ratios of SSTR2 expression to create a standard by which quantitative PET signals can be related to T cells of known density within tumors. Using the lentivirus developed in this study, the surface expression of SSTR2 in transduced Jurkat T cells was in the range of several million per cell, a level significantly higher than previously published (19) and therefore likely to extend the lower limit of SSTR2 + T cell detection. We observed that with a known threshold of radiotracer uptake, one can detect tumor-infiltrating T cells down to a minimum density of 0.8% or ~4 × 10 6 cells/cm 3 , with 95% specificity and 87% sensitivity.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Concerning the biodistribution of 68 Ga-DOTATOC in normal organs of nude mice, our data are consistent with those reported by other teams (21,22), although the engrafted tumours in their studies were derived from the pancreatic tumour cell line AR4-2J, with low %ID/g in all normal organs except in the kidneys. In humans, 68 Ga-DOTATOC PET is significantly taken up in the pancreas, which we and another team did not observe in nude mice (23).…”
Section: Discussionmentioning
confidence: 96%